Experimental and Simulation Study on the Dissolved Amount and Dissolution Rate of Supercritical CO(2) in Polystyrene Melt - Wang, Duyang (ACS Omega, 2019)
[Image: see text] The amount of supercritical CO(2) dissolved in polystyrene (PS), dissolution rate, and solubility under static conditions at 170–190 °C and 7.5–9.5 MPa were calculated by utilizing volume-changing-method experiments and numerical simulations. By comparison, the instantaneous error can be guaranteed to be less than 15%. The two results are in good agreement, and the reliability of the simulation method is verified. Based on the obtained results, another parameter was added to the tested model, and the dissolution rate of supercritical CO(2) in PS under different shear conditions was numerically simulated. The effects of temperature, pressure, and shear rate on dissolution were analyzed. The results show that when the temperature and pressure are constant, the dissolution rate of supercritical CO(2) in PS with shear increases significantly compared with that without shear. The conditions that enable the maximum dissolution rate are 190 °C, 9.5 MPa, and a shear rate of 240/π. With the abovementioned pressure and shear rate conditions, the maximum solubility can be obtained under the temperature of 170 °C.